Plasma Membrane Localization of CD36 Requires Vimentin Phosphorylation; A Mechanism by Which Macrophage Vimentin Promotes Atherosclerosis - Kim, Seo Yeon; Jeong, Se-Jin; Park, Ji-Hae; Cho, Wonkyoung; Ahn, Young-Ho; Choi, Youn-Hee; Oh, Goo Taeg; Silverstein, Roy L.; Park, Young Mi (Frontiers in Cardiovascular Medicine, 2022)
Vimentin is a type III intermediate filament protein expressed in cells of mesenchymal origin. Vimentin has been thought to function mainly as a structural protein and roles of vimentin in other cellular processes have not been extensively studied. Our current study aims to reveal functions of vimentin in macrophage foam cell formation, the critical stage of atherosclerosis. We demonstrated that vimentin null (Vim–/–) mouse peritoneal macrophages take up less oxidized LDL (oxLDL) than vimentin wild type (Vim+/+) macrophages. Despite less uptake of oxLDL in Vim–/– macrophages, Vim+/+ and Vim–/– macrophages did not show difference in expression of CD36 known to mediate oxLDL uptake. However, CD36 localized in plasma membrane was 50% less in Vim–/– macrophages than in Vim+/+ macrophages. OxLDL/CD36 interaction induced protein kinase A (PKA)-mediated vimentin (Ser72) phosphorylation. Cd36–/– macrophages did not exhibit vimentin phosphorylation (Ser72) in response to oxLDL. Experiments using phospho-mimetic mutation of vimentin revealed that macrophages with aspartate-substituted vimentin (V72D) showed more oxLDL uptake and membrane CD36. LDL receptor null (Ldlr–/–) mice reconstituted with Vim–/– bone marrow fed a western diet for 15 weeks showed 43% less atherosclerotic lesion formation than Ldlr–/– mice with Vim+/+ bone marrow. In addition, Apoe–/–Vim–/– (double null) mice fed a western diet for 15 weeks also showed 57% less atherosclerotic lesion formation than Apoe–/– and Vim+/+mice. We concluded that oxLDL via CD36 induces PKA-mediated phosphorylation of vimentin (Ser72) and phosphorylated vimentin (Ser72) directs CD36 trafficking to plasma membrane in macrophages. This study reveals a function of vimentin in CD36 trafficking and macrophage foam cell formation and may guide to establish a new strategy for the treatment of atherosclerosis.